Anesthetic management of argon laser photocoagulation in patients with premature retinopathy: Single center three-years experience of 178 cases (Annals of Medical Research, 2021)
Aim: The better survival rate of extremely low birth weight preterm infants results in retinopathy of prematurity (ROP). Blindness due to ROP can be prevented with urgent treatment started within 72 hours. A preterm infant always presents a great challenge to the anesthetists. Laser photocoagulation treatment under general anesthesia possesses extreme risks due to sharing the limited area with the surgeon. We aimed to present our experience of anesthetic management of premature infants receiving general anesthesia during laser photocoagulation treatment of ROP. Materials and Methods: Data belonging to a total of 159 former preterm infants that had 178 laser photocoagulation under general anesthesia between January 1st, 2013, and December 31st, 2015 were evaluated retrospectively in a period of three-years. Demographic and medical data were recorded from pre-anesthetic assessment sheets. Anesthesia induction technique, airway and pain management, peri/post operative adverse events, need for intubation were also recorded from anesthesia charts. Results: There was no significant difference between the stage of ROP and gender. Among 159 infants 13 of them were from twin-births and 5 of them were from triplet-births. Number of infants, who previously had general anesthesia for a surgical procedure other than laser photocoagulation, was 10 (%5.6). Most common surgical operation performed was explorative laparotomy for ileus (%2.8). Mean duration of anesthesia was 78.12±34.8 min (min-max 20-210). Mean birth weight of the infants was 1334±398g (min-max 480-2330). Mean gestational age at birth was 29.37±2.5 w (min-max 23-35 w).Conclusion: In the light of our results, with an experienced anesthetic and neonatal team, general anesthesia with sevoflurane can be performed safely to perform an immediate return to their preoperative hemodynamic and consciousness state at the end of the procedure. The need for further prospective data regarding the management of this vulnerable patient group is still evident.
Keywords: General anesthesia; premature; retinopathy of prematurity